2021
DOI: 10.1167/iovs.62.2.33
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Signaling Pathway Regulates the Proliferation and Differentiation of Rat Meibomian Gland Epithelial Cells

Abstract: Purpose Meibomian glands play a vital role in maintaining ocular surface stability. This study aimed to investigate whether Hedgehog signaling is involved in the regulation of meibomian gland epithelial cells. Methods Rat meibomian glands epithelial cells (RMGECs) were isolated from ducts and ductules, and then were cultivated to passage two on Matrigel coated wells in meibomian gland epithelial cells medium (MGECM). Cells were switched from MGECM to differentiation med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The “hedgehog signaling pathway” (ko04340), which regulates cell fate, including proliferation, apoptosis, migration, and differentiation ( Qu et al, 2021 ; Wutka et al, 2014 ), was significantly enriched in cell cluster 2. Ccnd2, which was significantly upregulated in cell cluster 2, is a key gene in the “hedgehog signaling” pathway ( Li et al, 2020 ) ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…The “hedgehog signaling pathway” (ko04340), which regulates cell fate, including proliferation, apoptosis, migration, and differentiation ( Qu et al, 2021 ; Wutka et al, 2014 ), was significantly enriched in cell cluster 2. Ccnd2, which was significantly upregulated in cell cluster 2, is a key gene in the “hedgehog signaling” pathway ( Li et al, 2020 ) ( Figure 1E ).…”
Section: Resultsmentioning
confidence: 99%
“…However, they evaluated the cornea and conjunctiva, but not the meibomian glands. Qu et al reported the antagonistic role of hedgehog signaling in the proliferation and differentiation of rat MGECs, suggesting that the PKA pathway might play a role in the differentiation of MGECs because the PKA pathway is an antagonist of hedgehog signaling [ 6 ]. In this study, we treated HMGECs with forskolin to increase cAMP levels and evaluated CREB phosphorylation to elucidate the role of the PKA pathway in lipid synthesis in meibocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of the CD147-mediated pathway was associated with a lower number of acini and a decrease in lipid-filled meibocytes in CD147 knockout mice [ 5 ]. The hedgehog signaling pathway has an antagonistic effect on the proliferation and differentiation of rat meibomian gland epithelial cells [ 6 ]. Transcriptome analysis revealed multiple pathways, such as the insulin signaling pathway, mammalian target of rapamycin pathway, and peroxisome proliferator activator receptor (PPAR) signaling, which are possibly associated with lipid synthesis in HMGECs and mouse meibocytes [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on our recent finding, DNase2 is a differentiation marker expressed in the central differentiated epithelial cells of the MGs but not in the peripheral undifferentiated cells [ 14 ]. It has been demonstrated that the self-renewal of acinar cells might be regulated by the Hedgehog pathway [ 16 ], which is a family of secreted proteins. It plays a role in regulating the genes of transcription involved in proliferation and differentiation [ 37 ].…”
Section: Physiology Of Mgmentioning
confidence: 99%
“…The abnormal proliferation and differentiation of meibocytes are the main causes of MGD rather than the hyperkeratinization of the ductal system [ 9 , 10 , 13 ]. Recent studies from our laboratory suggested that the co-effects of the hyperkeratinization of the ducts and the abnormal self-renewal of the acinar cells lead to MGD [ 14 , 15 , 16 ]. In addition, bacteria have a critical role in the occurrence of MGD [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%